CAPTURING TEACHING MOTIVATION OF TEACHER IN THE DISADVANTAGED AREAS - Hanggara Budi Utomo; Dewi Retno Suminar; Hamidah Hamidah (LPMPP Universitas Negeri Yogyakarta, 2019)
Teaching motivation of teachers is very important for student’s development. The purpose of this study is to test the teaching motivation of teachers in disadvantaged areas affected by the school climate and self-concept through the satisfaction of basic psychological needs. The subjects of this research were 241 teachers. Data collection techniques used instruments in the form of a school climate scale, a scale of self-concept, a scale of basic psychological need satisfaction, and a scale of teaching motivation. The data analysis techniques used a structural equation modeling. The results showed that the attention of teachers who teach in disadvantaged areas shows that the school climate and teacher’s self-concept differently provide an important role in teaching motivation mediated by the basic psychological needs satisfaction. This means that teaching motivation is a result of the role of the school climate as an external factor and satisfaction of basic psychological needs and self-concept as an internal factor. The implication of this research is the need for programs to develop teacher motivation in disadvantaged areas by optimizing and considering school climate, self-concept, and satisfaction of basic psychological needs as influential factors.